Urban Area Elementary Student Teaching Program - Minnesota Univ., Minneapolis; Minnesota Univ., Minneapolis ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
To prepare prospective elementary teachers for inner-city schools, this program was initiated at the University of Minnesota. Background knowledge concerning the family, the child, and the community gives the student teachers an understanding of the sources of problems encountered in inner-city classrooms. Resource people from the community and public schools bring expertise in urban sociology; poverty; the culture of black, Indian, and Mexican Americans; communication and how it is affected by cultural differences; classroom techniques relevant to the inner-city classroom--creative drama, role-playing and the use of multi-ethnic materials. Special attention is given to the techniques of teaching the basic skills and classroom management. Integral parts of the program are: (1) the careful screening of student candidates and cooperating teacher, (2) the joint school-university appointment of inner-city classroom teachers to coordinate the program and supervise the students, and (3) the development of an advisory committee, made up of representatives from both institutions, to assist in planning, evaluating, and recommending improvements in the program. Among the values have been that the number of students per quarter has increased from an average of 17 in 1964 to an average of 60 in 1969, that approximately two thirds of the student participants have chosen to remain as inner-city teachers, and that 11 groups involved have offered positive and supportive cooperation. (Author/JES)
ERIC Note: Entry for 1970 American Association of Colleges for Teacher Education Distinguished Achievement Awards.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College School Cooperation; Differentiated Staffs; Inner City; Practicum Supervision; Teacher Selection; Cooperative Programs; Minority Group Teachers; Student Teaching; Teacher Education Curriculum; Urban Teaching